The Influence of Promotion and Price on Buyer Satisfaction of Luwak White Coffee Products at Pondok Aren Distributors - Yulianty, Indri Nova; Pasaribu, Veta Lidya Delimah (Asian Journal of Applied Business and Management, 2024)
The purpose of this research is to determine the effect of promotion and price on purchase satisfaction for Luwak Whitee Coffee products at Pondok Aren Distributors. The method used is a quantitative method. The sampling technique used Slovin sampling and a sample of 99 respondents was obtained from a total population of 9388 agent shops in a year. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination, and hypothesis tests. The results of this research were that the hypothesis test obtained a calculated t value > t table or (9,531 > 1.984). Then promotion and price simultaneously have a significant effect on purchase satisfaction with the regression equation Y = 7,728 + 0.236X1 + 0.511X2. . The value of the coefficient of determination or contribution of influence is simultaneously equal, while the remainder is (100-52.3%) = 47.7% influenced by other factors. Hypothesis testing obtained a calculated F value > F table or (6,499 < 1.984).